2006
DOI: 10.1080/13607860600648080
|View full text |Cite
|
Sign up to set email alerts
|

Measuring sensory processing patterns of older Chinese people: Psychometric validation of the adult sensory profile

Abstract: The Adult Sensory Profile (ASP) evaluates the sensory experiences of adults in the categories of auditory, visual, taste/smell, touch, movement, and activity level. It generates four sensory processing patterns including low registration, sensation seeking, sensory sensitivity, and sensation avoiding. This study examined the psychometric properties of the Chinese version of ASP (ASP-CV) for older Hong Kong Chinese adults. Ninety-six participants with normal cognitive functioning and 33 participants with dement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 29 publications
3
30
2
1
Order By: Relevance
“…This result was expected because these two quadrants were related to each other and to low threshold quadrants (3). The Adolescent/ Adult Sensory profile has been translated into Chinese and was found to be a reliable and valid measure of sensory processing functions of older Hong Kong Chinese individuals [19].…”
Section: Instrumentmentioning
confidence: 91%
“…This result was expected because these two quadrants were related to each other and to low threshold quadrants (3). The Adolescent/ Adult Sensory profile has been translated into Chinese and was found to be a reliable and valid measure of sensory processing functions of older Hong Kong Chinese individuals [19].…”
Section: Instrumentmentioning
confidence: 91%
“…28 While, other studies also reported increased sensory sensitivity among older females, and they explained this sensitivity due to hormonal changes occurring in older females. 7,11,29 Similarly, a few studies have also investigated this issue among children and found that boys are less sensitive compared to girls in the various sensory domains. 5,9,22 The present study has several limitations.…”
Section: Dovepressmentioning
confidence: 99%
“…7,8 Previous research has indicated that problems in sensory processing may present in adulthood and affect functional performance and participation in ADL, 3 mental health problems, social participation, and quality of life. [9][10][11] Therefore, it is necessary to study sensory processing difficulties among different age groups and their impact on daily functioning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older adults tend to notice less sensory stimulation, engage in less sensory seeking behaviors, and have difficulties inhibiting irrelevant stimuli (Chung, 2006). The dementiabiological model has suggested that neurological changes in the brain and severe brain deterioration are possible factors affecting normal perception and processing of sensory information in older adults with dementia (Chung, 2006).…”
Section: Sensory Modulation In Older Adults With Dementiamentioning
confidence: 99%